A STUDY OF VISUAL OUTCOME AND COMPLICATIONS OF SCLERAL-FIXATED INTRAOCULAR LENS - KAMLESH NAJUKRAM LANJE; RAJESH B GOTEKAR; SREELAKSHMI PILLAI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Objectives of this study are to find indications for the scleral-fixated intraocular lens, to measure visual acuity in patients with scleral-fixated intraocular lens postoperatively and also to note the complications of scleral-fixated intraocular lens intra and postoperatively. Materials and Methods: The study includes 36 eyes of 36 aphakic patients presenting to Ophthalmology department between November 2019 and April 2021 after obtaining Institutional Ethical Committee Clearance. Informed and written consent were obtained from each patient included in the study. Goldmann applanation tonometer was used to record IOP for all cases preoperatively. Detailed ophthalmic examination was done on slit-lamp biomicroscope and best corrected visual acuity was recorded. Keratometry was done using an autorefractokeratometer. The axial length of the eye was calculated with the help of A scan biometry in aphakic mode. IOL power was then calculated with the SRK T formula using 118.2 as A constant for SFIOL. Patients underwent anterior vitrectomy followed by scleral fixation intraocular lens implantation by Gabor’s technique after the detailed preoperative examination. The postoperative examination was done on day 1, day 7, at 1 month, and at 3 months, and the findings were noted. Result: Out of 36, 25 (69%) patients were having surgical aphakia due to complications of cataract surgery. 5 (14%) patients were having aphakia due to trauma to the eye and 6 (17%) patients were having spontaneous dislocation of lens. Good visual outcome was observed postoperatively. Improvement in BCVA to 6/18 or more was observed in all 36 (100%) patients at the end of 1 month. Corneal edema, AC flare, vitreous hemorrhage, and increase in intraocular pressure were some of the complications that were noted in the immediate postoperative period. However, all the complications had resolved at the end of 1 month. Conclusion: From this study, we can conclude that combined anterior vitrectomy and scleral-fixated sutured PCIOL implantation is an effective and safe procedure to correct aphakia in eyes without adequate capsular support. It provides excellent visual outcome with less postoperative complications. Furthermore, it is a superior alternative to ACIOLs and iris-fixated IOLs as it decreases the complications such as bullous keratopathy, UGH syndrome, iritis, and CME.